Developing Law Students’ Creativity through Values-Based Legal Education: A Study of the Lecturer’s Role at Ummah Campus - Rahmad, Abdul; Alfiandi Zikra; Murthada; Yanti Arnilis; syafridhayanti (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2026)
This study aims to analyze the development of Law students’ creativity through values-based legal learning and to examine in depth the role of lecturers in designing, implementing, and evaluating the learning process at Ummah Campus. This research employed a qualitative approach with a case study design. The participants consisted of lecturers and students of the Law Study Program at Ummah Campus, selected through purposive sampling. Data were collected through participant observation of the learning process, in-depth interviews with lecturers and students, and document analysis of Semester Learning Plans (RPS), teaching modules, and student assignments. Data analysis was conducted through the stages of data reduction, data display, and inductive conclusion drawing. Data validity was ensured through source and technique triangulation, as well as member checking to confirm the credibility of the findings. The findings indicate that values-based legal learning emphasizing justice, integrity, responsibility, and humanity significantly contributes to the development of students’ creativity. Students’ creativity was reflected in their ability to formulate innovative legal arguments, conduct critical case analyses, and generate alternative solutions to contemporary legal issues. The role of lecturers proved to be highly strategic as facilitators, motivators, and role models in internalizing legal values. Lecturers who applied case discussions, problem-based learning, and court simulation methods were able to encourage divergent and reflective thinking among students. Furthermore, a dialogical academic environment that is open to differing perspectives strengthened the creative climate in the classroom. This study provides both theoretical and practical implications. Theoretically, the findings enrich the discourse on the integration of values education in fostering creativity in higher education, particularly in legal studies. Practically, the results recommend strengthening lecturers’ pedagogical capacities through training in values-based learning strategies and innovative legal teaching methods. The institution is also encouraged to formulate academic policies that support reflective, collaborative, and contextual learning to ensure the sustainable development of students’ creativity. This study is supported by interview instruments, classroom observation sheets, and samples of students’ creative outputs, including case analyses and reflective essays. All supplementary materials are available in supporting documents and can be accessed upon request from the corresponding author for academic purposes and research replication.